Silencing citizens how criminal groups create vacuums of justice - Miller, Andrew Cesare (Cambridge University Press, 2024)
Criminal groups, like mafias and gangs, often get away with murder. States are responsible for providing justice but struggle to end this impunity, in part because these groups prevent witnesses from coming forward with information. Silencing Citizens explains how criminal groups constrain cooperation with the police not just by threatening retaliation but also by shaping citizens' perceptions of community support for cooperation. The book details a social psychological process through which criminal group violence makes community support for cooperation appear weaker than it is and thus reduces witnesses' willingness to share information with the police. The book draws on a wealth of data including original surveys in two contrasting cities - Baltimore, Maryland in the Global North and Lagos, Nigeria in the Global South. This title is part of the Flip it Open Programme and may also be available Open Access. Check our website Cambridge Core for details